Control of turbulent and magnetohydrodynamic channel flows : boundary stabilization and state estimation - Vázquez, Rafael (Systems & control., 2008)
"This monograph presents new constructive design methods for boundary stabilization and boundary estimation for several classes of benchmark problems in flow control, with potential applications to turbulence control, weather forecasting, and plasma control. The book may be used as a supplementary text for graduate courses on control of distributed-parameter systems and on flow control."--Jacket